Answer:
15(1 + 3)
Step-by-step explanation:
15 written in its prime factors is 3 × 5 (15 × 1)
45 written in its prime factors 3 × 3 × 5 (15 × 3)
The greatest common factor is 15: 15 × 1 = 15 and 15 × 3 is 45
∴ 15 + 45 = 15(1 + 3)
Hope this helps! Make me brainiest, lol it's fine if you don't. : )
The next three terms are: -3, 6, and 15
To get each new term, we simply add 9 to the last term. So we add 9 to -12 to get -3. Then we add 9 to -3 to get 6. Finally we add 9 to 6 to get 15
In other words,
first term = -12
second term = first term+9 = -12+9 = -3
third term = second term + 9 = -3+9 = 6
fourth term = third term + 9 = 6+9 = 15
This process repeats forever though we only need three terms in this case.
So that's why the answer is the three values -3, 6 and 15
Answer:
46
Step-by-step explanation:
3 x 2^3 + 5^2 - 18/6
= 3 x 8 + 25 - 3
= 24 + 25 - 3
= 49 - 3
= 46
I think the correct answer from the choices listed above is option D. A polynomial function has a zero value at x=3 for the <span>expression where one factor is x-3. This factor when x=3 will always result to a zero value no matter what you multiply to it. Hope this answers the question.</span>